Produksi Susu dan Lama Laktasi Sapi Perah Friesian Holstein di PT Ultra Peternakan Bandung Selatan - Didin S Tasripin; Raden Febrianto Christi; Dimas Dwi Biyantoro (University of Insan Cendekia Mandiri, 2020)
The aim of this research was to know the production performance of Holstein Friesian dairy cow on first lactation based on milk production records and length of lactation. The research was done at PT. Ultra Peternakan Bandung Selatan, West Java. A method of the research used descriptive analysis. Milk production and length lactation period on first lactation were used as production performance variable. The data obtained from 2011-2015 production record of 750 dairy cows on first lactation. Production performance of dairy cows on first lactation were have average daily milk production of 18,94 ± 3,74 Kg, 359,29 ± 81,14 days on length of lactation, 102,19 ± 65,27 days on peak production. The highest daily milk production of dairy cows in the first lactation period was 29,06 Kg, the smallest was 4,76 Kg, the longest length lactation was 872 days and the shortest was 195 days.